Transaction Processing Model For XML Databases In Mobile Computing Environment - Radhamani, G. (2006)
With the remarkable growth of XML data over the Internet, different application areas have resulted in a growing number of XML databases, especially those involving web-based applications. This thesis focuses on a transaction processing model for XML databases in a mobile computing environment.